Manajemen Emosi Sedih Menurut Al-Qur'an: Kajian Surah Yusuf Ayat 86 dengan Pendekatan Psikologi - Iffaty Zamimah; Dinda Aulia Putri (Universitas Islam Negeri Syekh Wasil Kediri, 2021)
Many negative actions that people do to themselves and others are the result of their inability to manage their sad emotions. Whereas Allah has sent down the Qur'an to serve as a medicine and guidance for human existence. On this basis, this paper examines how to manage sad emotions according to the Qur'an's perspective in QS. Yūsuf (12): 86 using a psychological approach and describes steps that individuals may take to adopt sad emotion management in their life. This is a qualitative study that employs library research as well as an approach to the science of tafseer and psychology. The result is that the author concludes that the way of managing sad emotions that Prophet Ya‘qūb did was: At the height of his anger, disappointment, and sadness, Prophet Ya'qūb did not say despicable words to his children, but what he did displacement while being patient with ṣabrun jamīl. Then, the Prophet prayed to Allah to deliver him from the grief and suffering he was experiencing. Praying with full sincerity and thankfulness, as performed by the Prophet Ya‘qūb, had a significant impact on his mind and is one method for making the cognitive adjustment. Furthermore, the Prophet Ya‘qūb attempted to remedy the situation by instructing his children to find Yūsuf and his brother. Here Prophet Ya'qūb tries to do a problem-focused coping strategy by instructing his children to return to Egypt to find Yūsuf and his brother. Prophet Ya‘qūb used this instruction to try to conquer, accept, or dominate the circumstance by focusing on the emotion and problem and bringing it directly to the solution (coping).